Comparative effect of boiling, microwave and ultrasonication treatment on microstructure, nutritional and microbial quality of Tofu - Abiola Folakemi Olaniran; Faith Oluwatoyosi Agaja; Oluwatobi Victoria Obayomi; Seno Isidore Ebong; Adekunbi Adetola Malomo; Olubukola David Olaniran; Oluwakemi Christianah Erinle; Stephen Olugbemiga Owa (Applied Food Research)
Ultrasonic and microwave methods are innovative techniques for enhancing plant-based meat alternatives improving both the products and processes. Tofu is a commonly used meat substitute worldwide and serves as a rich source of both protein and minerals obtained from soybeans. This research examined the effect of application microwave and ultrasonic technologies during production of tofu on the quality attributes and shelf stability compared to boiling a conventional method. The freshly prepared soymilk was divided into three batches, which were then subjected to different pre-treatment methods, namely: boiling, microwave, and ultrasonication, where the Boiled tofu (BTU) served as the control. The findings of the study revealed that ultrasonicated tofu (18 × 102cfu/g) had the least microbial load after 42 days of storage compared to microwaved (28 × 103cfu/g) and boiled tofu (25 × 105cfu/g). The antioxidant activities and total flavonoid contents (TFC) of tofu samples ranged from 22.2 to 35.5 mg/mL with ultrasonicated tofu (UTU) showing the highest scavenging activity (at 47.40 % and 22.2 mg/mL). The cavitation forces enhanced the homogeneity the protein gel and provide tofu with a denser and even texture. Thus, the applications ultrasonication in the production of Tofu, as it had the lowest microbial population after 42 days of storage, conserved the nutritional value, highest free radical scavenging and the preservation of antioxidant properties in Tofu samples, compared to boiling or microwaving processing method. Thus ultrasonication is a viable options for industrial production for quality and a highly gelatinous Tofu.